Ice Camp (PRELIMINARY) position/heading (hourly). (ASCII). Version 1.0 [PRELIMINARY] ... - McPhee, M.; University Of Washington (UCAR/NCAR - Earth Observing Laboratory, 2007)
Hourly record of GPS drift velocities and position from the Ice Station. Data are smoothed through a complex filter. Period covered from 10/14/1997 through 09/25/1998 with a few gaps. ...